A Comparison of Buyback and Trade‐In Policies to Acquire Used Products for Remanufacturing. Issue 3 (24th May 2017) - Cole, Dwayne; Mahapatra, Santosh; Webster, Scott
Abstract : We study how acquisition policies for used products as a source for a remanufactured consumer product affect system performance. We introduce a consumer choice model of new product purchase and used product return, which is consistent with the classic Bass diffusion model of sales over time. We capture new and remanufactured product sales, the evolution of the install base, and consumer return and repurchase decisions over the life cycles of new and remanufactured product. Our analyses lead to two main findings on the acquisition policies. First, if the buyback price is less than the margin of a new product, then a trade‐in policy is likely to yield higher profit than a buyback policy. Second, we show that the profitability is highest when the time lag between the introduction of a new product and initial demand for a remanufactured version of the product is at or near the sweet spot, which is the age of the product at which the costs of acquisition and remanufacturing are at minimum. Further, when the time lag between the introduction of a new product and initial demand for its remanufactured version is near the sweet spot, then simple pricing methods are close to optimal.